Providing Biological Plausibility for Exposure-Health Relationships for the Mycotoxins Deoxynivalenol (DON) and Fumonisin B1 (FB1) in Humans Using the AOP Framework - van den Brand, Annick D; Bajard, Lola; Steffensen, Inger-Lise; Brantsæter, Anne Lise; Dirven, Hubert A A M; Louisse, Jochem; Peijnenburg, Ad; Ndaw, Sophie; Mantovani, Alberto; De Santis, Barbara; Mengelers, Marcel J B (Toxins, 2022)
Humans are chronically exposed to the mycotoxins deoxynivalenol (DON) and fumonisin B1 (FB1), as indicated by their widespread presence in foods and occasional exposure in the workplace. This exposure is confirmed by human biomonitoring (HBM) studies on (metabolites of) these mycotoxins in human matrices. We evaluated the exposure-health relationship of the mycotoxins in humans by reviewing the available literature. Since human studies did not allow the identification of unequivocal chronic health effects upon exposure to DON and FB1, the adverse outcome pathway (AOP) framework was used to structure additional mechanistic evidence from in vitro and animal studies on the identified adverse effects. In addition to a preliminary AOP for DON resulting in the adverse outcome (AO) 'reduced body weight gain', we developed a more elaborated AOP for FB1, from the molecular initiating event (MIE) 'inhibition of ceramide synthases' leading to the AO 'neural tube defects'. The mechanistic evidence from AOPs can be used to support the limited evidence from human studies, to focus FB1- and DON-related research in humans to identify related early biomarkers of effect. In order to establish additional human exposure-health relationships in the future, recommendations are given to maximize the information that can be obtained from HBM.
Keywords: Mycotoxins; HBM4EU; mycotoxins; trichotheceny; Adverse Outcome Pathways; dráhy škodlivých účinků; fumonisiny; Trichothecenes; mykotoxiny; Fumonisins; FB1: fumonisin B1; zvířata; Humans; viabilita buněk; Cell Survival; DON: deoxynivalenol; HBM: human biomonitoring; human biomonitoring for Europe; AOP: adverse outcome pathway; lidé; Animals